Anatomical Assessment of Cephalic Vein and Superficial Branch of Radial Nerve Using High-Resolution Ultrasound Imaging - Inui, Atsuyuki; Mifune, Yutaka; Nishimoto, Hanako; Kurosawa, Takashi; Yamaura, Kohei; Mukouhara, Shintaro; Yoshikawa, Tomoya; Kuroda, Ryosuke (Journal of Hand and Microsurgery, 2021)
Introduction The superficial branch of the radial nerve (SBRN) has a risk of nerve injury during cephalic vein (CV) cannulation. Due to the lack of imaging study regarding SBRN and CV relationship, we analyzed the anatomical relationship between the SBRN and the CV using ultrasound (US) imaging.Materials and Methods In total, 82 upper limbs of 41 healthy volunteers were analyzed. The SBRN and CV were identified at the following three points in the elbow extension and pronation position: at the radial styloid process (point 1), 5 cm proximal to point 1 (point 2), and 10 cm proximal to point 1 (point 3).Results The distance between the SBRN and CV was 1.1 ± 1.0 mm at point 1, 1.3 ± 1.3 mm at point 2, and 2.1 ± 1.6 mm at point 3. The depth of the SBRN from the surface of the skin was 2.7 ± 0.9 mm at point 1, 3.5 ± 1.1 mm at point 2, and 5.5 ± 1.9 mm at point 3. The percentage of the SBRN that ran beneath the CV was 17.5%, 53.5%, and 92.4% at points 1, 2, and 3, respectively.Conclusion Ultrasonography can reveal the anatomical relationship between the SBRN and CV.
Keywords: superficial branch of radial nerve; cephalic vein; ultrasound